(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This work aims at describing how nudging and behavioural insights can be a significant and proportional contribution to the pandemic response activities. To this end, the first part will be devoted to an analysis of the main characteristics and implications of behavioural techniques. The focus will then move to the role nudges have come to play in the health sector, thus justifying their employment in the fight against the new coronavirus. It will then be showed that western democracies, through the establishment of nudge units and an assessment based on the proportionality principle, seem more suitable to an ethical integration of behavioural tools in their public policies.